Reactive oxygen species derived from NADPH oxidase as signaling molecules regulate fatty acids and astaxanthin accumulation in Chromochloris zofingiensis - Yuan, Yi; Zhao, Tiantian; Gao, Weizheng; Ye, Wenqi; Chen, Yuling; Sun, Dongzhe; Zhang, Zhao (Frontiers in Microbiology, 2024)
Abiotic stresses can increase the total fatty acid (TFA) and astaxanthin accumulation in microalgae. However, it remains unknown whether a unified signal transduction mechanism exists under different stresses. This study explored the link between NADPH oxidase-derived reactive oxygen species (ROS) and the accumulation of fatty acids and astaxanthin in Chromochloris zofingiensis under three abiotic stresses. Results showed significant increases in fatty acid, astaxanthin, and ROS levels under nitrogen deficiency, phosphorus deficiency, and high-salinity stress. The introduction of the NADPH oxidase inhibitor DPI decreased the content of these components. This underscores the pivotal role of NADPH oxidase-derived ROS in the accumulation of fatty acid and astaxanthin under abiotic stress. Analysis of transcriptomes across three conditions following DPI addition revealed 1,445 shared differentially expressed genes (DEGs). Enrichment analysis revealed that biotin, betalain, thiamine, and glucosinolate may be important in stress responses. The heatmap demonstrated that DPI notably suppressed gene expression in the fatty acid and carotenoid biosynthesis pathways. Our findings underscore the pivotal role of NADPH oxidasederived ROS in the accumulation of fatty acid and astaxanthin under abiotic stresses.